Recent advances in risk factors associated with ocular exfoliation syndrome. Issue 2 (17th November 2019) - Ghaffari Sharaf, Mehdi; Damji, Karim F.; Unsworth, Larry D.
Abstract: Exfoliation syndrome is generally considered a progressive age‐related systemic disorder of the extracellular matrix, which is clinically characterized through the observation of flaky white aggregates on ocular tissues. Exfoliation syndrome is directly linked to exfoliative glaucoma in elderly patients, where it is known as the most common identifiable cause of open‐angle glaucoma. Despite the identification of various risk factors associated with exfoliation syndrome, the exact pathogenesis of this syndrome has not been fully elucidated. There is a growing number of genome‐wide association studies in different populations around the world to identify genetic factors underlying exfoliation syndrome. Besides variants in LOXL1 and CACNA1A genes, new loci have been recently identified which are believed to be associated with exfoliation syndrome. Among different genetic factors, functional variants might help to better understand mechanisms underlying this systemic disorder. Besides genetic factors, epigenetic regulation of different gene expression patterns has been thought to play a role in its pathogenesis. Other factors have been also considered to be involved in the development of exfoliation syndrome at cellular organelles level where mitochondrial impairment and autophagy dysfunction have been suggested in relation to exfoliation syndrome. This review addresses the most recent findings on genetic factors as well as cellular and molecular mechanisms involved in both the development and progression of exfoliation syndrome.